Expert System for Early Detection of Child Intelligence Development Using Website-Based Multiple Intelligence - Abdul Rochim; Hindarto (Universitas Muhammadiyah Sidoarjo, 2022)
Every child when born into the world, he brings various types of innate intelligence unique to one another. Children's intelligence is one aspect of the child's initial ability to understand every pattern and understanding in thinking. Multiple intelligences are one of the intelligences that can help find characteristics in early childhood. With this expert system, it is hoped that it can become a medium for parents to find the dominance of intelligence in early childhood. The method of identifying children's intelligence used in this system uses forward chaining and certain factors which retrieve intelligence data from several sources and published journals. The results that this researcher wants is to find dominance intelligence in early childhood as well as an assessment of user satisfaction with the application.